THE DIFFERENCES IN FUNCTIONAL AND MOTOR INDICATORS BETWEEN THE PROFESSIONAL GROUPS OF KARATE AND JUDO FEMALE COMPETITORS - Dr Patrik Drid; Sandra Vujkov (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2007)
Training session which is being held in the frame of schedule and working program, also in the frame of preparation of professional karate and judo competitors, holds a signifi cant infl uence to particular functional and motor capabilities. The subject of investigation is differences in functional and motor indicators between two select groups.